Analisis Kemudahan User Dalam Menggunakan Aplikasi “HADIR” dengan Metode TAM - Fira Aulia Nadia; Adinda Tria Suci (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This rapidly growing technology can make it easier for anyone to use it for various activities, such as more efficient and effective employee attendance activities. The development of information technology to make it easier for users to complete their work. The 'Present' application is an application that helps employees and admins to start from attendance to calculating employee payroll. This study aims to identify the extent to which users can easily use this application by applying the TAM (Technology Acceptance Model) method which involves evaluation variables such as recognized utility, perceived ease of use, attitude towards use, intention to use, and actual user. Questionnaires have been distributed online to respondents who are employees of PT. Kokowi Kuliner Indonesia, which is currently using the application. The findings of this study indicate that the factor that influences the user's ease of use in the application is the level of perceived ease of use intention, namely the variable perceived ease of use (ease) on intention to use (intention). And PT. Kokowi Kuliner feels dissatisfied with the use of the